2006
DOI: 10.1111/j.1747-0765.2006.00010.x
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur starvation reduces phytosiderophores release by iron-deficient barley plants

Abstract: The aim of the present study was to examine the effect of sulfur (S) supply on the response to iron (Fe) deficiency in graminaceous plants. Barley seedlings (Hordeum vulgare L. cv. Europa) were cultured hydroponically for 10 days at three S levels (0, 60 and 1200 µmol L −1 sulfate) with (+Fe) or without (−Fe) 100 µmol L Fe uptake that was as high as the level of S supply. The results support the view that S availability can influence either the release of phytosiderophores or the ability to take up Fe from an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
54
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 19 publications
3
54
0
1
Order By: Relevance
“…It has been demonstrated that S deWciency may limit the release of PS and Fe uptake in barley roots, thus leading to a reduced accumulation of Fe in the leaf tissue (AstolW et al 2006a). Furthermore, it has been shown that Fe deWciency caused an increase in 35 SO 4 2¡ uptake rates in maize and barley plants (AstolW et al 2004(AstolW et al , 2006b.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It has been demonstrated that S deWciency may limit the release of PS and Fe uptake in barley roots, thus leading to a reduced accumulation of Fe in the leaf tissue (AstolW et al 2006a). Furthermore, it has been shown that Fe deWciency caused an increase in 35 SO 4 2¡ uptake rates in maize and barley plants (AstolW et al 2004(AstolW et al , 2006b.…”
Section: Discussionmentioning
confidence: 98%
“…Interactions between S and Fe nutrition have been shown in Strategy II plants (Kuwajima and Kawai 1997;AstolW et al 2003AstolW et al , 2004AstolW et al , 2006aBouranis et al 2003), indicating that S deWciency could limit Fe-deWciency response through a decrease in the production and release of PS.…”
Section: Introductionmentioning
confidence: 98%
“…Gene mRNA levels were normalized with respect to the internal control EF1; relative changes in gene expression were calculated on the basis of their expression levels in Fedeficient plants. Bars represent means ± SD of transcript levels on 2 independent experiments with 3 replicates; capital letters refer to statistically significant differences between treatments (t-test, P<0.05) which limited the uptake of exogenous Fe-PS complexes from the external medium (Astolfi et al 2006). …”
Section: Discussionmentioning
confidence: 99%
“…This idea is also supported by the higher uptake rate and translocation of 35S recorded in Fe deprived plants. Interestingly, it was shown that the availability of SO/-can affect accumulation (Kuwajima and Kawai 1997) and release (Astolfi et al 2004) of phytosiderophores in Fe-deficient barley roots.…”
Section: Discussionmentioning
confidence: 99%